Simulation study of GaN-based HFETs with graded AlGaN barrier. (July 2015) - Zhou, Xingye; Feng, Zhihong; Fang, Yulong; Wang, Yuangang; Lv, Yuanjie; Dun, Shaobo; Gu, Guodong; Tan, Xin; Song, Xubo; Yin, Jiayun; Cai, Shujun
Highlights: The trapping behaviors in GaN HFETs with graded AlGaN barrier are investigated. Both the DC characteristics and transient responses of the device are simulated. Two rising trends caused by the bulk and surface traps are observed for the transient current. HFET with graded AlGaN barrier has better immunity to the surface traps. Abstract: GaN-based heterostructure field-effect-transistors (HFETs) with graded AlGaN barrier, in which the Al mole fraction of Al x Ga1− x N ranges from 0 to a certain value (e.g. 35%), demonstrated the potential for high-linearity applications. Based on the two-dimensional (2-D) device simulations, in this paper the trapping effects and current collapse in GaN-based HFETs with graded AlGaN barrier are investigated and analyzed. First, both the carrier profile and direct current (DC) characteristics of the device are obtained for calibration of the simulation model, and the simulation results matched the experimental measurement data very well. In addition, the transient responses of GaN-based HFETs with graded AlGaN barrier are simulated to study the trapping behaviors. As the time increases, two rising trends are observed for the transient current, which are caused by the bulk acceptor traps and surface donor traps, respectively. By comparing with the conventional GaN-based HEMT, the results show that the HFET with graded AlGaN barrier has better immunity to the surface traps, leading to smaller current collapse.